CUT&RUN for Chromatin Profiling in Caenorhabditis elegans. Issue 6 (17th June 2022) - Emerson, Felicity J.; Lee, Siu Sylvia
Abstract: Cleavage under targets and release using nuclease (CUT&RUN) is a recently developed chromatin profiling technique that uses a targeted micrococcal nuclease cleavage strategy to obtain high‐resolution binding profiles of protein factors or to map histones with specific post‐translational modifications. Due to its high sensitivity, CUT&RUN allows quality binding profiles to be obtained with only a fraction of the starting material and sequencing depth typically required for other chromatin profiling techniques such as chromatin immunoprecipitation. Although CUT&RUN has been widely adopted in multiple model systems, it has rarely been utilized in Caenorhabditis elegans, a model system of great importance to genomic research. Cell dissociation techniques, which are required for this approach, can be challenging in C. elegans due to the toughness of the worm's cuticle and the sensitivity of the cells themselves. Here, we describe a robust CUT&RUN protocol for use in C. elegans to determine the genome‐wide localization of protein factors and specific histone marks. With a simple protocol utilizing live, uncrosslinked tissue as the starting material, performing CUT&RUN in worms has the potential to produce physiologically relevant data at a higher resolution than chromatin immunoprecipitation. This protocol involves a simple dissociation step to uniformly permeabilize worms while avoiding sample loss or cell damage, resulting in high‐quality CUT&RUN profiles with as few as 100 worms and detectable signal with as few as 10 worms. This represents a significant advancement over chromatin immunoprecipitation, which typically uses thousands or hundreds of thousands of worms for a single experiment. The protocols presented here provide a detailed description of worm growth, sample preparation, CUT&RUN workflow, library preparation for high‐throughput sequencing, and a basic overview of data analysis, making CUT&RUN simple and accessible for any worm lab. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Growth and synchronization of C. elegans Basic Protocol 2 : Worm dissociation, sample preparation, and optimization Basic Protocol 3 : CUT&RUN chromatin profiling Alternate Protocol : Improving CUT&RUN signal using a secondary antibody Basic Protocol 4 : CUT&RUN library preparation for Illumina high‐throughput sequencing Basic Protocol 5 : Basic data analysis using Linux